In a New Guise/Brief Notes - Davidson, Alan E (Petits Propos Culinaires, 1990)
Paula Wolfert: Good Food from Morocco, John Murray, London, 1989: 224 pp, index, £15.95. Paula Wolfert: The Cooking of South-West France, DK, London, 1987: 320 pp, index, £8.99. Marcella Hazan: The Second Classic Italian Cookbook, Papermac, London, 1987: 414 pp, index, £8.99. Martha Rose Shulman: Chez Martha Rose, Macmillan, London, 1988: 352 pp, index, £8.99. Richard Olney: Simple French Food, Penguin Books Ltd, London, 1990: 339 pp, index, £8.99. Leslie Forbes: A Table in Tuscany, Penguin Books Ltd, London, 1987: 159 pp, index, £7.99. Sri Owen: Indonesian and Thai Cookery, Piatkus , London, 1988: 128 pp, index, £6.95. Yan-Kit So and Paul Bloomfield: Party Eats, Piatkus , London, 1988: 128 pp, index, £6.95. Patricia Lousada: Game Cookery, John Murray, London, 1989: 227 pp, index, £15.95. Philippa Scott: Gourmet Game - Recipes and Anecdotes from Around the World, Barrie & Jenkins, London, 1989: 160 pp, index, £14.95. Lesley Blanch: From Wilder Shores - The Tables of My Travels, John Murray, London, 1989: 160 pp, index, £14.95.